Study on Temporal Alterations in Land Cover Types in Simien Mountain National Park, Northwest Ethiopia - Masresha, Getinet (International Journal of Sustainable Agricultural Research, 2019)
This study was carried out in Simien Mountain National Park (SMNP) of Ethiopia to trace the temporal dynamics in land use types from the information generated through the analysis of land sat images. Results revealed that throughout the study period, variable extent of changes was observed in land use classes. In the first reference period (1972 - 1994), agricultural (9945.56 ha) and barren land (3066.6 ha) showed a remarkable increment whereas other land use types were decreased. In the second reference period (1994 - 2017), montane forest, grassland and shadow showed increasing trend with the dramatic change in grassland. In the first reference period (1972 - 1994), maximum negative rate of change was observed for Erica forest with deceleration rate of 83 ha/year which continued in the 2nd reference period (1994 - 2017) with the change decreasing rate of 16.6 ha/year. Maximum positive rate of change (74.6 ha/year) was observed for agricultural land followed by barren land (68.6 ha/year). In the second reference period maximum positive rate of change was observed for grassland with accelerated rate of change 260.5 ha/year whereas maximum deceleration rate (272.8 ha/year) was observed for agricultural land. At present, montane forest cover is increasing whereas agricultural land is decreasing dramatically contributing for the restoration of the ecosystem. However, intensified grazing was identified as a principal driver affecting ecological process in the Park; therefore, a long term strategy should be designed to meet the sustainable utilization of natural resources in the Park.